Upaya Pencegahan Penyebaran Covid-19 dan Penyakit Menular melalui Pembuatan Hand Sanitizer - Kun Ika Nur Rahayu; Devangga Darma Karingga; Mujtahid Bin Abd. Kadir (Universitas Pahlawan Tuanku Tambusai, 2026)
Communicable diseases including COVID-19 remain a public health problem that requires prevention efforts based on community empowerment. This community service activity aimed to improve the knowledge and skills of the community in the working area of Sukorame Public Health Center, Kediri City, in producing hand sanitizer containing 60% alcohol with aloe vera as an additional ingredient. The method used was an educational-participatory approach through health education, discussion, demonstration, hands-on practice, mentoring, and evaluation using pre-tests, post-tests, and skill observation. The results showed an increase in the good knowledge category from 17.8% to 77.8% after the education session. In addition, 84.4% of participants were able to independently produce hand sanitizer according to the procedure. This activity shows that education and practical training are effective in improving community capacity for preventing communicable diseases. The results of this community service are important as a form of community empowerment to support sustainable clean and healthy living behavior.